KONSEP MAHRAMIYAH DALAM ISLAM (Analisis Pertimbangan Pimpinan Al Misbah Al Aziziyah Samalanga Terhadap Peraturan Santriwati) - Saipul Bahri (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
Mahram is a person who is forbidden to marry, Al Misbah Al Aziziyah is one of the Islamic boarding schools or Islamic boarding schools in Samalanga which does not escape several regulations, one of the regulations made by the head of public relations is that when students return to their hometown or leave the Islamic boarding school, they must be accompanied by mahrams. As for the Al-Misbahul Azizyah Islamic Dayah regulations for the public relations section: students who return to the village and return to the Islamic boarding school must be accompanied by a mahram. In making short trips, less than two marhalah, such as students who leave the dayah who only go to the Samalanga market for important purposes, are accompanied by public relations, and are under the supervision of the dayah. In traveling to Walimatul Ursy and pilgrimage, it is permitted to have less than two marhalahs or more accompanied by the dayah teachers and the dayah leaders. The results of the study concluded that mahrams are people who are forbidden to marry forever, such as fathers, children, brothers, uncles and others. Mahram is divided into muabbad (eternal obstacles), namely because of lineage, marriage and breastfeeding, mahram muaqqat (temporary obstacles) is a temporary/temporary prohibition, which is something that comes new and can disappear one day. Al Misbah Al Aziziyah student traveling regulations: students who return to their hometown are required to be picked up by the guardian of the student who has mahram status in the Shari'a or by the parents of the student, permission hours are opened apart from study hours and sleep/rest hours, female students are required to wear clothes determined politeness. The consideration of Al-Misbah Al-Aziziyah Samalanga's leadership regarding the mahram rules for female students is due to the Ummah's concern as the leader of Al-Misbah Al-Aziziyah towards students and teachers who have been studying for a long time where many students ask their friends who are female students at Al Another Al-Alziziyah Misbah to come to the ursy walimatur and the place of their mourning because they don't have many friends in the village because they have been studying for a long time so their friends are none other than the students at the boarding school. Keywords: Samalanga, Al-Alziziyah, Students, Teachers and Mahram